Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s10696-021-09429-4
|View full text |Cite
|
Sign up to set email alerts
|

Leasing or selling? The channel choice of durable goods manufacturer considering consumers’ capital constraint

Abstract: In this paper, we explore how a monopoly manufacturer chooses the market strategies and decides the optimal price to obtain maximum profit. We divide the market into the C-type market and the N-type market, and analyze the profitability of the monopoly manufacturer who takes the pure-selling, pure-leasing and hybrid strategy respectively, considering consumers' capital constraint and the life span of the durable goods in an indefinite time horizon model. ( 1) We find that a larger proportion of the consumers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…Consumers value the leased product as αv, and α(α ≥ 0) is used to denote consumer preferences for leasing. A similar assumption can be seen in recent studies of product leasing [3][4][5].…”
Section: Problem Description and Modelingsupporting
confidence: 79%
See 2 more Smart Citations
“…Consumers value the leased product as αv, and α(α ≥ 0) is used to denote consumer preferences for leasing. A similar assumption can be seen in recent studies of product leasing [3][4][5].…”
Section: Problem Description and Modelingsupporting
confidence: 79%
“…Consumers may have financial limitations and are sensitive to products' prices. e model established by Li et al discussed this issue and found that manufacturers offer products to consumers at low prices through leasing, which expands the market coverage and creates price discrimination [4]. Gilbert et al [5] analyzed how per-use rentals and sales differentiate consumers within the framework of a hybrid selling-leasing model.…”
Section: Selling Versus Leasingmentioning
confidence: 99%
See 1 more Smart Citation
“…The second paper by Li et al (2021) considers leasing and selling strategies of a monopoly manufacturer of durable goods. In this paper, a model with two differentiated markets is built, and three basic market strategies are examined, including a pure-selling strategy, a pure-leasing strategy, and a hybrid strategy.…”
Section: The Papers In the Special Issuementioning
confidence: 99%
“…The analytical methods used in these papers include predictive analytics, optimization, simulation, as well as hybrid methods. Two papers focus on supply chain problems, one on information sharing by Dominguez et al (2021) and one on leasing and selling strategies by Li et al (2021)). Two papers consider scheduling and dispatching problems in manufacturing, one in flexible manufacturing by Zanchettin (2021) and one on lean manufacturing by Mezzogori et al (2021).…”
mentioning
confidence: 99%